Between love and loathing - Rose, Shain ([place of publication not identified] : Page & Vine, an Imprint of Meredith Wild LLC, 2023)
Fake dating my enemy so I can design my dream bakery should be easy $1! = (Bas long as I don$1 (Bt fall in love with him.s
Series statement from author's website.
Keywords: Man-woman relationships -- Fiction; Bakeries -- Fiction; Bakers -- Fiction; Wills -- Fiction; Billionaires -- Fiction; Romance fiction; Erotic fiction